Partial Replacement of Coarse Aggregates with Plastic Waste in Paver Blocks - Olubunmi, Adetoye; Olamoju, Rabiu Olayemi; Taiye, Afolayan (Journal of Sustainability and Environmental Management, 2023)
Plastics are widely used worldwide, but their non-biodegradable nature leads to significant waste generation. Improper management of plastic waste poses environmental hazards. Paver blocks made of concrete offer versatility, aesthetic appeal, and low maintenance when manufactured and placed correctly. Utilizing plastic as a building material aligns with Sustainable Development Goals. Concrete production contributes to the depletion of natural resources like aggregates. This study investigates the partial replacement of coarse aggregates with plastic waste in pavement blocks, using a mix ratio of 1:2:4. Coarse aggregates were replaced at volumes of 0%, 5%, 10%, and 15%. After batching and mixing, 54 cubes were produced and cured for 7, 14, and 28 days. Tests conducted included slump, compressive strength, and water absorption. The results indicate an optimal replacement of 10% of coarse aggregates with plastic waste which reduced water absorption. Plastic waste is recommended for use in low-load bearing walls and structures like pedestrian footpaths and water retaining structures, reducing costs and conserving natural resources. Effective utilization of plastic waste in the construction industry benefits the environment.